The Complex Phenomenon Of Community Education: The Lives And Socio-Psychological Resilience Of Indonesian Migrant Workers In Malaysia - Ahyar; Saleh, Muhammad; Nurul Yaqinah, Siti; Amrulloh, Zaenudin; Hadi, Syamsul; Bin Ibrahim, Abdullah; Khairul Aiman Bin Wan Mokhtar, Wan (TASAMUH, 2025)
The number of Indonesian Migrant Workers has increased significantly from year to year. However, this increase in numbers is not accompanied by guarantees of protection obtained from the state. Various cases related to migrant workers are increasing, ranging from legal protection to life protection. This research will examine the complexity of the problems of Indonesian migrant workers in terms of the life and social security experienced by Indonesian migrant workers. This research shows that the socio-psychological experiences of migrant workers center on life learning gained through job satisfaction and its consequences. Meanwhile, in terms of human capital (community education), migrant workers receive little good learning that focuses on problems and the creativity of migrant workers in solving their problems. There is also a lack of experience among migrant workers in integrating new information with their experiences.